An Analysis of Teacher-Student Interactions in EFL Class at SMP Ihsaniyah Tegal - Sulistyawati, Anin Eka; Taufiqulloh, Taufiqulloh; Yuliani, Vika (Jurnal Bahasa Inggris, 2021)
This study presents the analysis of the teacher-student interactions in online and offline EFL classes. The objectives of this study are to identify the teacher-student interactions and to analyze the implementation of the types of teacher-student interactions in EFL classes. It is descriptive qualitative research involving three English teachers and thirty students for each class at SMP Ihsaniyah Tegal as the participants of the research. The data were collected through direct classroom observation and videos taken in the class. The data were analyzed based on a FLINT System. The results in this study by observation from the three teachers showed that the type of ‘Asks Question’ from the teachers’ talks and ‘Student Response Open-Ended’ from the students’ talks had the highest percentage. It means that teachers wanted the students to be more active and braver to speak in English. The conclusion of this study indicated that the dominant types of teacher-student interactions in EFL classes are ‘Asks Question’ from the teachers’ talks and ‘Student Response Open-Ended’ from the students’ talks because the teacher tended to act as a facilitator that facilitated students to speak and be more active and as a resource providing the information needed by students. In addition, the students had more opportunities to speak and interact in EFL class by giving responses to the teachers’ talks.